Accumulation of periostin in acute exacerbation of familial idiopathic pulmonary fibrosis - Murata, Keisuke; Koga, Yasuhiko; Kasahara, Norimitsu; Hachisu, Yoshimasa; Nunomura, Satoshi; Nakajima, Nozomi; Yokoo, Hideaki; Kaira, Kyoichi; Maeno, Toshitaka; Dobashi, Kunio; Izuhara, Kenji; Hisada, Takeshi (Journal of Thoracic Disease, 2018)
Periostin, an extracellular matrix molecule, is associated with idiopathic pulmonary fibrosis (IPF). It is known that the frequency of familial IPF (FIPF) ranges from 0.5% to 2.2% among IPF cases. However, the relationship between periostin and FIPF has not been previously described. We report the first case of periostin accumulation in the lungs of a patient with an acute exacerbation of FIPF. A 72-year-old woman, diagnosed with FIPF, had been followed up for 5 years. The patient experienced increased dyspnea within a 1-month period and was referred to our hospital. The patient was hypoxic, and chest computed tomography showed rapidly expanding bilateral reticular shadows. Despite pulse-steroid and intravenous-cyclophosphamide therapy, the patient died 25 days after admission. On admission, serum periostin levels were not significantly elevated, while serum fibrotic marker levels were elevated. Immunohistochemical analysis of the lungs on autopsy showed marked accumulation of periostin in the active fibrotic lesions, whereas intact and burned-out areas did not show significant expression of periostin. This case might provide insight into the role of periostin in acute exacerbation of IPF.